The effectiveness of the Media Smart Program on promoting the critical thinking of children towards the use of celebrities in television advertising - Magalhães, Ana Filipa Veloso de (2010)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics